A depth‐sensing technique on 3D‐printed compensator for total body irradiation patient measurement and treatment planning. Issue 11 (27th October 2016) - Lee, Min‐Young; Han, Bin; Jenkins, Cesare; Xing, Lei; Suh, Tae‐Suk
Abstract : Purpose: The purpose of total body irradiation (TBI) techniques is to deliver a uniform radiation dose to the entire volume of a patient's body. Due to variations in the thickness of the patient, it is difficult to produce such a uniform dose distribution throughout the body. In many techniques, a compensator is used to adjust the dose delivered to various sections of the patient. The current study aims to develop and validate an innovative method of using depth‐sensing cameras and 3D printing techniques for TBI treatment planning and compensator fabrication. Methods: A tablet with an integrated depth‐sensing camera and motion tracking sensors was used to scan a RANDO™ phantom positioned in a TBI treatment booth to detect and store the 3D surface in a point cloud format. The accuracy of the detected surface was evaluated by comparing extracted body thickness measurements with corresponding measurements from computed tomography (CT) scan images. The thickness, source to surface distance, and off‐axis distance of the phantom at different body section were measured for TBI treatment planning. A detailed compensator design was calculated to achieve a uniform dose distribution throughout the phantom. The compensator was fabricated using a 3D printer, silicone molding, and a mixture of wax and tungsten powder. In vivo dosimetry measurements were performed using optically stimulated luminescent detectors. Results: The scan of the phantom took approximately 30 s. The mean error for thickness measurements at each section of phantom relative to CT was 0.48 ± 0.27 cm. The average fabrication error for the 3D‐printed compensator was 0.16 ± 0.15 mm. In vivo measurements for an end‐to‐end test showed that overall dose differences were within 5%. Conclusions: A technique for planning and fabricating a compensator for TBI treatment using a depth camera equipped tablet and a 3D printer was demonstrated to be sufficiently accurate to be considered for further investigation.